UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE PROYEK PADA SISWA KELAS IX.2 SMP NEGERI 6 LUBUK BASUNG SEMESTER GANJIL TAHUN PELAJARAN 2019/2020 - Linda Purwanti (Universitas PGRI Sumatera Barat, 2023)
This research emerged from the issues faced in mathematics education in class IX.2 of SMP Negeri 6 Lubuk Basung, where a significant number of students exhibited low enthusiasm, creativity, and absorption of course materials, resulting in suboptimal learning outcomes. Therefore, to enhance student learning outcomes in mathematics, the Project-Based Learning method was implemented in class IX.2 of SMP Negeri 6 Lubuk Basung. The research results from each cycle of action taken during mathematics instruction in class IX.2 of SMP Negeri 6 Lubuk Basung using the Project-Based Learning method demonstrated improvements in both the learning process and student learning outcomes. This improvement is evident in student achievement, as the pre-cycle showed an average learning outcome of 62 with a mastery level of 53.4%. In the first cycle, student learning outcomes reached a mastery level of 63.3% with an average score of 69, while in the second cycle, a substantial improvement was observed with an average score of 82 and a mastery level of 86.6%. Therefore, it can be concluded that the use of the Project-Based Learning method enhances student learning outcomes in mathematics in class IX.2 of SMP Negeri 6 Lubuk Basung.